PENERAPAN METODE LEARNING TOGETHER PADA MATA PELAJARAN FIQIH MATERI THAHARAH DALAM MENINGKATKAN HASIL BELAJAR SISWA DI KELAS VII MTS MUALLIMIN UNIVA MEDAN - Hasibuan, Ajimahrani (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
The learning outcomes of Grade VII students of Thaharah subject Fiqh are still low. This happens because the delivery of subject matter by the teacher is dominated by the use of lecture methods and less linking the subject matter with the real world, so students are less active in learning. To achieve optimal results, teachers need to use learning methods that can help students associate subject matter with students' daily lives, so learning becomes more meaningful. The method is learning together. This study uses a class action research design which was conducted in two cycles. Each cycle consists of four stages, namely planning, action, observation, and reflection. The subjects of this study were 36 students of grade VII of MTs Muallimin Univa Medan. Data collection techniques are done through tests and non-tests (observation and documentation). Indicators of success in this study are the average grade of ≥ 75 and the percentage of classical learning completion 75%, and student involvement in learning activities ≥ 75%. Research shows an increase in student learning outcomes, student learning activities from cycle I to cycle II. In the first cycle, the average value of student learning outcomes reached 70.69 and the percentage of classical learning completion 69.44%, while in the second cycle the average learning outcome was 81.39 and the percentage of classical learning completion was 86.11%. The involvement of students in learning cycle I was 71.76% and cycle II became 78.40%. Based on these results, it can be concluded that the learning together learning method can improve the activities and student learning outcomes in learning the Fiqh of Thaharah material in class VII MTs Muallimin Univa Medan. Therefore, teachers can use the learning together method as an alternative learning approach to improve the quality of learning in school